Comparative Analysis Between Project-Based Learning (PJBL) and Conventional Learning (KBM) in the Student Learning Process - Muhammad thoriqhabib habib; Daniel Situmorang; Siti Zahara Simanjuntak; Rifael David Fransisco; Meski Egianta Sitepu; Hendra Gunawan Manalu; Ikhwan El Akmal Manalu (EDUCATION JOURNAL OF INDONESIA, 2026)
This study comparatively evaluates the effectiveness of Project-Based Leaming (PBL) and conventional learning (KBM) in the student learning process at Universitas Satya Terra Bhinneka. The research background is rooted in the paradigm shift of 21st century education, which demands the development of critical thinking, collaboration, creativity, and authentic problem-solving skills. A quantitative approach with a quasi-experimental non-equivalent control group design was used to compare student engagement and leaming outcomes of both instructional models. Data collection instruments in the form of questionnaires descriptively revealed that the majority of students perceived PjBL, as superior in terms of active learning, soft skills development, and workplace readiness compared to KBM, although preferences regarding understanding of difficult concepts showed more varied responses. These findings align with meta-analyses demonstrating that PjBL makes a positive contribution to learning outcomes and 21st-century skilis compared to traditional methods. The results indicate that PjBL is capable of promoting active student engagement and higher non-cognitive skill development, supports the relevance of learning to the real world, and provides recommendations for higher education curriculum development in Indonesia. Keywords: Project-Based Learning, Conventional Learning, Learning Process, 21st Century Skills.